PENERAPAN METODE PEMBELAJARAN MIND MAPPING PADA MATA PELAJARAN FIQIH KELAS VIII DI MTsN 08 AGAM - Afridho Achmad; Darul Ilmi; Salmi Wati; Wedra Aprison (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
The problems faced in learning Fiqh in class VIII MTsN 8 Agam include lack of student focus and chatting activities that interfere with concentration. The use of the mind mapping method by teachers has not been fully effective, because many students have difficulty in imagining and creating, only making mind maps without understanding them, and not following guidelines such as using curved lines or colors. This research is descriptive qualitative, aiming to describe the application of the mind mapping method in the classroom. Data were collected through observation, interviews, and documentation, with teachers as the main informants and students as supporting informants. The results showed that the mind mapping method had been applied according to the steps outlined by Tony Buzan. In addition, the teacher also uses the lecture method to improve students' understanding. This method helps students understand the material more easily and increases their creativity in learning.